1976
DOI: 10.1099/00207713-26-4-511
|View full text |Cite
|
Sign up to set email alerts
|

Moraxella atlantae sp. nov. and Its Distinction from Moraxella phenylpyrouvica

Abstract: A homogeneous group of gram-negative, rod-shaped, and oxidase-positive bacterial strains, growing with small colonies, is described. In ordinary culturalbiochemical tests, the entity appeared most similar to Moraxella phenylpyrouvica, although it has so far been distinguished from that species by its simultaneous lack of urease and phenylalanine and tryptophan deaminase activities, inability to grow on solid medium at 4 to 1073, relative salt sensitivity, and different behaviour on bile-containing media. The f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

1979
1979
2020
2020

Publication Types

Select...
5
3
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…The sequence differences between the two Psychrobacter species amounted to 5.7% as well. The suggestion that these species could be classified as separate genera is in correspondence to earlier reports based on 16S rRNA gene sequencing (8), DNA-DNA hybridization (10), and DNA transformation (2).…”
Section: Case Reportsupporting
confidence: 61%
“…The sequence differences between the two Psychrobacter species amounted to 5.7% as well. The suggestion that these species could be classified as separate genera is in correspondence to earlier reports based on 16S rRNA gene sequencing (8), DNA-DNA hybridization (10), and DNA transformation (2).…”
Section: Case Reportsupporting
confidence: 61%
“…On the other hand, pitting is common with M. lacunata, whose colonies are smaller and form dark haloes on chocolate agar. Rod-shaped Moraxella species, especially M. atlantae and M. lincolnii, are more fastidious and display smaller colonies on SBA, less than 1 mm in diameter after 24 h. Colonies of M. atlantae are small (usually 0.5 mm in diameter) and show pitting and spreading (24). The growth of M. atlantae is stimulated by bile salts, which explains its growth on MacConkey agar.…”
Section: Genotyping and Epidemiologymentioning
confidence: 99%
“…P-clade Moraxella have more similar phenotypes compared to M-clade Moraxella than to Psychrobacter strains. Review of type strain descriptions revealed that Psychrobacter are consistently urease positive, nitrate reducing, salt tolerant, and non-fastidious, whereas P-clade Moraxella are inconsistent with their urease and nitrate reducing phenotypes, are sensitive to high salt concentrations, andare often nutritionally fastidious -they have complex growth requirements (in particular, often blood or bile for growth)[23,24,39,42,50,51,66,67].…”
mentioning
confidence: 99%